Development of green composite: Pineapple Leaf Fibers (PALF) Reinforced Polylactide (PLA) - Rose Farahiyan, Munawar; Nurul Hayati, Jamil; Mohd Khairul Shahril, Mustaq Ahmad; Skh Muhammad, Skh Abdul Rahim; Muhammad Zaimi, Zainal Abidin; Mohd Asyadi Azam, Mohd Abid; Lau, Kok Tee (Trans Tech Publications, 2015)
Green composite material has become the most desired material to replace polymer composites made from fossil oil. Besides having advantages over its biodegradability and quality performances, the material sources are abundant and renewable. Therefore, this research focused on developing green composite which is derived from a combination of pineapple leaf fibers (PALF) and Polylactide (PLA). PALF is extracted from pineapple leaves which are easily found during harvesting pineapple plantation. In order to study the influences of different fibres characterization, the fibres were extracted from different types of pineapple available in Malaysia, namely Moris Gajah, Jasopine, Maspine, and N36. The main objective of this study was to investigate the physical and mechanical properties of this green composite. The physical testing was carried out to determine water absorption while the tensile and bending tests were conducted for mechanical testing. For the purpose of comparing the material properties, PALF reinforced polypropelene (PP) was developed too. Based on the result, Jasopine fibre shows the highest tensile and flexural strength for the combination of both polymers in comparison to the other types of PALF.